Features of the ATP and diadenosine tetraphosphate effect on ADP-induced platelet aggregation at pre-eclampsia - Bakunovich, Andrei V.; Zinchenka, Anatoly I.; Bulanava, Klavdiya Ya. (Journal of the Belarusian State University. Ecology, 2020)
In vitro experiments established significant increase in the aggregation degree of pregnant women platelets with pre-eclampsia in response to the action of ADP, compared with a physiological pregnancy. Experiments revealed that diadenosine-5’,5’’’-P1,P4-tetraphosphate and ATP-Mg2+ are able to exert an inhibitory effect on ADP-induced platelet aggregation during pre-eclampsia. The potential advantage of Ap4A and its derivatives as therapeutic agents is that they have a synergistic inhibitory effect on the P2Y1 and P2Y12 platelet receptors and have a longer half-life in the bloodstream compared to ATP. The research results suggest using Ap4A as a substrate for the development of drugs aimed at reducing the increased functional activity of platelets during pre-eclampsia.